The Shifting Natural Wealth of Nations : The Role of Market Orientation - Arezki, Rabah; van der Ploeg, Frederick; Toscani, Frederik (World Bank, Washington, DC, 2018)
This paper explores the effect of market orientation on (known) natural resource wealth using a novel dataset of world-wide major hydrocarbon and mineral discoveries. Consistent with the predictions of a two-region model, the empirical estimates based on a large panel of countries show that increased market orientation causes a significant increase in discoveries of natural resources. In a thought experiment whereby economies in Latin America and sub-Saharan Africa remained closed, they would have only achieved one quarter of the actual increase in discoveries they have experienced since the early 1990s. The results call into question the commonly held view that natural resource endowments are exogenous.